The Contribution of Trust and Anxiety in Health Care During the CoViD-19 Pandemic (Studia Doctoralia Psychology and Educational Science, 2024)
This research aims to extend the knowledge about trust and state anxiety in the relationship between patients and medical professionals, by focusing on the specific situation of medical treatments. This study aims to see if patients' trust in the resort, medical staff and treatment plays a role in decreasing state anxiety. Methods. Patients enrolled in the resort’s treatment base (N = 798) after the signing of an informed consent, they were asked about their state and trait anxiety, resilience, general trust (GTR) and fear of CoViD-19 (FCO) during the pandemic restrictions. State anxiety and FCO were measured longitudinally, more exactly on the first day, middle period and at the end of the treatment, whilst GTR, resilience and trait anxiety were measured only in the first day of the process. Results. The results show a significant decrease in state anxiety influenced by GTR and FCO and trait anxiety too. Resilience played a factoring role, but the result is not significant. Conclusions. The results of this study show that the state anxiety of patients with high trust in physicians decreases during the treatment. Since these results are especially robust, they can inform future research and medical practice. Therefore, is important to acknowledge that the integration of psychological components in patients’ treatmentis unquestionably necessary.